Masalah Perundungan (Bullying) di SD dan Cara Pencegahannya - Intan Afrina Safira; Ari Suriani (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
Bullying in elementary schools is a social problem that negatively impacts children’s psychological, social, and academic development. This study aims to examine the various forms of bullying occurring in elementary school settings, the underlying causes, and effective, sustainable prevention strategies. The research employs a qualitative descriptive approach, collecting data through observation, interviews, and document analysis. Findings reveal that bullying in elementary schools includes physical, verbal, social, and cyberbullying forms, which often go undetected due to underreporting. Contributing factors involve family environment, parenting styles, school supervision, and weak character education. Effective bullying prevention requires a comprehensive approach involving character education based on empathy and tolerance, teacher training, parental involvement, and firm yet educative anti-bullying policies. In conclusion, collaboration among all stakeholders in creating a safe and inclusive school environment is crucial to reducing bullying behaviors and supporting children’s optimal development.